Mutual relationship between taboo of faith and house space: A case study of "licit architecture" in 70 Rai, Khlong Toei, slum improvement project area, Bangkok, Thailand. Issue 4 (7th August 2021) - Abe, Takuya; Shimizu, Ikuro
Abstract: This paper aims at understanding the mutual relationship between the taboo of faith and a house space in the "licit architecture" in 70 Rai, Khlong Toei, a slum improvement project area in Bangkok, Thailand. In another paper, we defined a house in this area as "licit architecture, " which is built by architectural practices of people, such as deviating from official laws, customary laws, and customs within an acceptable level. This concept works not only for understanding the actual practices of the people in this area but also provides a deeper understanding of how they can survive in the serious living and spatial conditions in the slum. In this paper, we focus on various taboos relating to Buddhism and the spiritual faith and practices seen in house spaces with such licit architectures. Through a detailed description of these points, we show how a taboo relationship influences the layout, orientation, elevation, and removal of a house space. We point out that the "licit architecture" concept can be expanded broadly if we consider the architectural practices of the people, particularly various taboos of the removal, layout, orientation, and elevation, and how the people face these taboos. Abstract : We defined the house in the area as "licit architecture, " which is built by architectural practices of people such as to deviate from official law, customary law, and custom within the acceptable level among them. This paper aims at the understanding of the mutual relationship between taboo on faith and house Space in "licit architecture" in 70 Rai, Klongtoey, the slum improvement project area, Bangkok, Thailand.